Integrated Thematic Teaching Materials With Microsoft Sway Based on Problem-Based Learning Model in Elementary School - Bima Prakarsa Arzfi; Desyandri Desyandri; Yeni Erita; Zelhendri Zen (Universitas Negeri Padang, 2023)
Microsoft Sway is one of several software developed by Microsoft to present information in a way that is easy to understand. This research aims to create integrated thematic teaching materials with Microsoft Sway-based Problem-Based Learning models in grade V SD that are valid and instant The procedure used in this research is an R&D procedure that uses the ADDIE development model. The results obtained from this product development research are from the module expert validator getting a score of 92.8%, the media/graphic expert validator getting a score of 90%, and the language expert validator getting a score of 95%, each of which is categorized as very valid. For the practicality questionnaire, the reaction of educators and student participants received a score of 93.33% and 92.85%, both of which were categorized as very instant. This research concludes that it can create integrated thematic teaching materials with the Problem-Based Learning model based on Microsoft Sway in grade V SD which is very valid and very practical.